(untitled) (Research, Society and Development, 2021)
The article aimed to show in the scientific literature information about the technologies and tools used in combat with COVID-19. It is a literature review, where the bibliographic survey was carried out through the databases: Scientific Eletronic Library Online (SCIELO), Medical Literature Analysis and Retrieval System Online (MEDLINE), ScienceDirect e Business Source Complete (EBSCO). The inclusion criteria for the papers were: articles published between 2019 and 2020, full texts, available in full, in Portuguese, English and Spanish. For exclusion: monographs, theses, review articles, gray literature and repeated articles, resulting in 13 articles at the end of the research. The studies brought broad and different approaches to research on technologies, innovations and COVID-19, such as: mobile applications, telehealth, development of protective masks, safe and effective training for healthcare professionals, among others. The pandemic and the crisis in the health sector evidenced with COVID-19 served as a fertile field for the creation and adaptation of technologies to assist in coping with cases, becoming fundamental to the care practice. In this perspective, innovative tools have emerged to combat the COVID-19 epidemic worldwide.